Shuttle in the sky the Columbia disaster - Krumm, Brian (North Mankato, Minnesota Capstone Press, 2016)
"Describes the events before and after the Columbia disaster"-
A gift from book Africa
1 2 11 13
Keywords: Space Shuttle Program (U.S.) -- Juvenile literature; Columbia (Spacecraft) -- Juvenile literature; Columbia (Spacecraft) -- Accidents -- Juvenile literature